Lifestyle Transformations of the Orang Asli through Participations in the Palm Oil Plantation Projects in Terengganu State, Peninsula Malaysia - Ramle, Abdullah; Mohamad Hafis, Amat Simin; Asmawi, Ibrahim (2014)
The Orang Asli are one of the indigenous ethnics, with its majority living in suburban and remote areas of Peninsula Malaysia. Such settlement patterns result in their traditional economy being synonymous with hunting and gathering activities. The poverty rates among Heads of Households (HoH) are also high. Statistics in 2008 showed a total of 13,946 (50.92 %) Orang Asli HoH as being poor with 9,004 (32.34 %) belonging to the hardcore poor group (JAKOA, 2011). Various efforts have been undertaken by the government to solve the problem. Implementation of the commercial crops project comprising palm oil and rubber are among the efforts undertaken extensively, and a number of them can be considered successful in alleviating the poverty rate. A study had been carried out on the local Orang Asli community in Terengganu to identify how the projects have impacted the socio-economic status and lifestyle transformations of the local residents. Data were collected through the process of observation techniques, interviews and document review. Study results showed that the implementation of commercial crops have now become instruments in improving the socio-economic transformation of HoH and transformations of the overall lifestyle. Based on income indicators, the average income of HoH has exceeded RM2,000.00 per month. This income is a substantial increase compared to the amount of income they received in the 1990s, which was below RM500.00 per month. In line with the income increase, community members no longer focus on traditional economic activities such as hunting and gathering, but began to shift to activities that enabled them to receive wages such as laborers in palm oil plantations. Similarly, such is the case in the usage and savings indicators. A large number of HoH can afford luxurious items including cars, while other HoH have bank savings as preparations for future use of family members.